Linguagem e morte na experiência lírica de Herberto Helder - Lima, Carmem Medeiros (2019)
This study analyses how the philosophical discourse configures literary discourse in the poems of the last work published in life of the poet Herberto Helder, A morte sem mestre, focusing on two main themes, language and death, in a phenomenological perspective from the philosophical studies of Giorgio Agamben. We will show up the moments the poetic language sometimes seems to be the solution of the human existence, sometimes this language proves inefficent, inconclusive, incapable of expressing the sensible truth, making us to think that the creative process of the poet is as arduous as that of facing death. In order to guide the research, we seek the dialogue between philosophy and poetry and we investigate two hypotheses: first, the death is compared to the process of the creation of the poetic language and for this reason it will be true only if the poetic Dasein will be aware of your finitude and second one, it shows up that the sensitive poetic writing is unable to express the essence of language, because only death can contain all the truth that is within Dasein. We will stand out in the four chapters the language elements of the poet’s universe, placing them in a mythical/sacred/profane reading and we will explore the meaning of death bringing philosophy conceptions for the study of texts, relating them with the arduous process of Portuguese poet’s creation which is discovered in the silence and in the impossible writing. “This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001.”